Os Peroneum Fracture: A Case Report - Deveci, Alper; Fırat, Ahmet; Daşar, Uygar; Akkaya, Mustafa; Bozkurt, Murat (Fırat University, 2012)
Os peroneum is seen as full ossified in approximately 20% of adults. Bipartite is a common appearance and it is seen in 30% of adults with the os peroneum . Fracture of the os peroneum is rare and it may occur after ankle injury. It is very difficult to distinguish between the os peroneum fracture and the bipartite os peroneum. Therefore, if there are complaints as swelling and pain in lateral of the foot especially around the cuboid after ankle injury, we should keep in mind that may be os peroneum fracture.

Os peroneum erişkinlerin yaklaşık % 20 kadarında tam ossifiye olarak görülür. Bipartit görünüm sık görülen bir durumdur ve os peroneumu olan erişkinlerin % 30'unda görülür. Os peroneum kırığı ayakbileği travması sonrası gelişebilen nadir görülen bir durumdur. Bipartite os peroneumdan ayrımı güçtür. Bu nedenle ayak bileği travması sonrası, ayak lateral alanında özellikle kuboid çevresinde hassasiyet ve şişlik gibi semptomların varlığında os peroneum kırığı olabileceği akılda tutulmalıdır.
Os Peroneum Kırığı: Olgu Sunumu